2020
DOI: 10.1038/s41586-020-2424-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural cells are key regulators of organ-specific immune responses

Abstract: The mammalian immune system implements a remarkably effective set of mechanisms for fighting pathogens 1 . Its main components are hematopoietic immune cells, including myeloid cells that control innate immunity and lymphoid cells that constitute adaptive immunity 2 . However, immune functions are not unique to hematopoietic cells, and many other cell types display basic mechanisms of pathogen defence 3 – 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
287
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(306 citation statements)
references
References 44 publications
19
287
0
Order By: Relevance
“…Notably, although this study did not include reproductive tissues such as the uterus, many of the identified immune genes and associated GOBP terms are reflected in our scRNAseq results, primarily enriched in F1 (defence response to virus, cellular response to IFNg, antigen processing and presentation). Our results further suggest that such roles can be attributed to specific subpopulations of cells, something that is not accounted for by methods employed by Krausgruber et al However, both reports highlight that structural cell populations may have previously underappreciated roles in tissue homeostasis out with the typical barrier/connective tissue functions (Krausgruber et al 2020).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Notably, although this study did not include reproductive tissues such as the uterus, many of the identified immune genes and associated GOBP terms are reflected in our scRNAseq results, primarily enriched in F1 (defence response to virus, cellular response to IFNg, antigen processing and presentation). Our results further suggest that such roles can be attributed to specific subpopulations of cells, something that is not accounted for by methods employed by Krausgruber et al However, both reports highlight that structural cell populations may have previously underappreciated roles in tissue homeostasis out with the typical barrier/connective tissue functions (Krausgruber et al 2020).…”
Section: Discussionsupporting
confidence: 46%
“…A role for human eSFs in modulating the immune response has been described using an in vitro co-culture system (Queckborner, et al 2020). More recently, using an elegant multi-omics profiling and integrative bioinformatics approach, an important role for so called structural cells (endothelial, epithelial cells; fibroblasts) in immune cell regulation has been confirmed in 12 organs of the mouse, during both homeostasis and in response to immunological challenges (Krausgruber, et al 2020). Notably, although this study did not include reproductive tissues such as the uterus, many of the identified immune genes and associated GOBP terms are reflected in our scRNAseq results, primarily enriched in F1 (defence response to virus, cellular response to IFNg, antigen processing and presentation).…”
Section: Discussionmentioning
confidence: 99%
“…Human endothelial cells express leukocyte function antigen-3, but not CD80, and can induce allorecognition of CD8 + and CD4 + cells (Hughes, Savage, & Pober, 1990). (Krausgruber et al, 2020). Of note, the protective effects of JNK inhibition in both endothelial cells and infiltrating lymphocytes observed here provide valuable information for the treatment of chronic nephritis and renal transplantation.…”
Section: Inhibition Of Mapk-jnk Down-regulates Mhc In 5/6nx Micementioning
confidence: 76%
“…We observed an upregulated expression of COL6A3 in CD4 + effector T cells and NK cells of asymptomatic conditions. COL6A3 encodes type VI collagen, and the expression of collagens in structure cells is expected to enhance their ability to interact with hematopoietic cells (Krausgruber et al, 2020). However, the expression of collagens in immune cells is less discussed, and we suspect they might also facilitate better interaction with structure cells.…”
Section: Immune Profiles Of T Cells and Nk Cells In Covid-19 Patientsmentioning
confidence: 96%